Enhancing the benefit of slide steering drilling systems in horizontal wells of unconventional reservoirs - Chu, Hengzhi; Xiong, Chao; Hu, Kaili; Guo, Yong; Shi, Yucai; Zhang, Bo (Frontiers in Energy Research, 2023)
The slide steering drilling system consisting of bent positive displacement motor (PDM) and MWD is widely used to continuously implement all wellpath control operations by alternately applying the slide drilling mode and compound drilling mode. Due to the large friction force on drilling string during slide drilling in horizontal section, it seriously affects drilling speed and horizontal extension ability. To drill long horizontal section fast and economically, the key is to increase the compound drilling proportion and decrease the alternative times of two drilling modes. According to the features of wavy or tortuous horizontal section and wellpath calculation models, the prediction and control method of compound drilling proportion of horizontal section is first established, and then its influencing factors and laws are analyzed and verified by an example. Theoretical research and drilling practice have shown that the compound drilling proportion in horizontal section depends on the build-up rate of slide drilling, the inclination and azimuth change rates of compound drilling, and is independent to the target area parameters and wellpath fluctuation ratio. In order to increase the compound drilling proportion and reduce the slide drilling frequency in horizontal section, it is necessary to increase the build-up rate of slide drilling properly and reduce the inclination and azimuth change rates of compound drilling as far as possible. This paper is helpful to enhance the benefit of slide steering drilling system in horizontal well of unconventional reservoir.